2005
DOI: 10.1074/jbc.m505499200
|View full text |Cite
|
Sign up to set email alerts
|

JLP Associates with Kinesin Light Chain 1 through a Novel Leucine Zipper-like Domain

Abstract: Scaffolding proteins exist in eukaryotes to properly assemble signaling proteins into specific multimeric functional complexes. JLP is a novel leucine zipper protein belonging to a family of scaffolding proteins that assemble JNK signaling modules. JLP is a proline-rich protein that contains two leucine zipper domains and a highly conserved C-terminal domain. We have identified kinesin light chain 1 (KLC1) as a binding partner for the second leucine zipper domain of JLP using yeast twohybrid screening. The int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
60
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 31 publications
(34 reference statements)
6
60
0
2
Order By: Relevance
“…Confocal microscopy was then performed in cells expressing relatively low levels of both proteins, because such conditions might more faithfully resemble the localization pattern of the endogenous proteins as observed for PIKfyve (12,43). Consistent with previous studies (37,38,41), in the confocal images we observed that overexpressed JLP L WT attained primarily cytoplasmic and perinuclear distribution. Intriguingly, closer inspection of the deconvoluted confocal images from individual sections taken through the middle of the cell revealed that the JLP L -positive perinuclear structures displayed tubular profiles (Fig.…”
Section: Pikfyve Interacts With the C-terminal Region Of Jlp/jip4supporting
confidence: 72%
“…Confocal microscopy was then performed in cells expressing relatively low levels of both proteins, because such conditions might more faithfully resemble the localization pattern of the endogenous proteins as observed for PIKfyve (12,43). Consistent with previous studies (37,38,41), in the confocal images we observed that overexpressed JLP L WT attained primarily cytoplasmic and perinuclear distribution. Intriguingly, closer inspection of the deconvoluted confocal images from individual sections taken through the middle of the cell revealed that the JLP L -positive perinuclear structures displayed tubular profiles (Fig.…”
Section: Pikfyve Interacts With the C-terminal Region Of Jlp/jip4supporting
confidence: 72%
“…We conducted in vitro rescue experiments with both wildtype and altered forms of JSAP1, including a mutant that has a substitution in the leucine zipper domain and cannot interact with KLC, 13 and a deletion mutant lacking the KHC-binding domain (KBD). 26 We used lentiviral vectors to express these wild-type and mutant JSAP1 forms as hemagglutinin (HA)-tagged proteins (designated HA-JSAP1-WT, -LZ and -ΔKBD) in primary hippocampal neurons.…”
Section: Jsap1 and Jlp Regulate Axonal Transport T Sato Et Almentioning
confidence: 99%
“…Plasmids-The expression vectors encoding murine S-tagged full-length JLP, JLP domains, and shJLP have been described previously (3,7). Expression vectors for FLAG-hJLP were constructed by subcloning PCR fragments into the EcoRI/ XhoI sites of the pCMV-Tag2B (Agilent Technologies) vector.…”
Section: Methodsmentioning
confidence: 99%
“…Of all the members characterized in the JIP family, JLP is characterized by the presence of two leucine zipper domains and a JNK binding domain in its N terminus and a conserved C-terminal domain, all of which functions in binding to and forming specific cell signaling complexes (3). Although JLP is ubiquitously expressed, previous studies have shown that the protein plays a role in regulating neurite outgrowth by interacting with SCG10 (4), activating JNK/p38 MAPK signaling (3), regulating cell migration by interacting with G␣12 and G␣13 (5,6), and functioning in vesicle transport by binding to kinesin light chain (KLC1) and dynein microtubule motor proteins (7). Recent studies have identified that JLP and JIP3 can interact with ADP-ribosylation factor 6 (ARF6), a small G protein that function in the regulating cytokinesis by transporting recycling endosomes to the cleavage furrow (8).…”
mentioning
confidence: 99%